Cotylegaleata iskenderunensis n. sp., the second known species of the rotifer family Cotylegaleatidae (Monogononta: Ploima) - Smet, Willem H. De; Bozkurt, Ahmet (Zootaxa, 2016)
Cotylegaleata iskenderunensis n. sp. is described from a freshwater wetland (Sariseki) at Iskenderun, Turkey. This is the second species within the genus. Cotylegaleata iskenderunensis n. sp. differs from the only known congener, C. perplexa De Smet, 2007, in the shape of the trunk and foot, and particularly the shape of the cotyle and the structure of the trophi. The diagnosis of the genus and family is amended.